2022
DOI: 10.1007/s11356-022-21521-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic and renal toxicity following the injection of copper oxide nanoparticles (CuO NPs) in mature male Westar rats: histochemical and caspase 3 immunohistochemical reactivities

Abstract: Copper nanoparticles are widely utilized in a variety of applications, including metal catalysts, semiconductors, heat transfer fluids in machine tools, and even in antibacterial medications. Forty mature healthy Westar rats were utilized in the current investigation and grouped randomly into four groups (n = 10 rats/group). Group I (G1) was kept as a control group, but G2, G3, and G4 were intraperitoneally injected with CuO NPs with a dose (5 mg, 10 mg, 25 mg/kg body weight/day) respectively for 9 days. Rats … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
5
11
0
Order By: Relevance
“…They reported the association of apoptosis with upregulation of caspase-3 protein immunoexpression in different tissues. 21 This aligns with a study by Dey et al They analyzed the toxicity of CuO-NPs and their ability to trigger apoptosis in cancer cells. They reported an increase in caspase-3 protein expression with statistical significance compared with the normal control group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…They reported the association of apoptosis with upregulation of caspase-3 protein immunoexpression in different tissues. 21 This aligns with a study by Dey et al They analyzed the toxicity of CuO-NPs and their ability to trigger apoptosis in cancer cells. They reported an increase in caspase-3 protein expression with statistical significance compared with the normal control group.…”
Section: Discussionsupporting
confidence: 86%
“…Ghonimi et al demonstrated that CuO-NPs had a toxic impact on hepatic and renal tissues, supporting this possibility. 21 Additionally, a previous study that evaluated the impact of oral exposure to CuO-NPs on the rats' liver revealed significant hepatotoxicity in OS. 22 This CuO-NPs' toxicity might return to the production of cellular ROS.…”
Section: Discussionmentioning
confidence: 99%
“…(2022) concluded in their investigative study that dosing with CuO NPs intraperitoneally for 9 consecutive days has a potential toxicity on liver and kidney tissues of male mature rats that may affect their functions [40]. On other hand, results of this study found an improvement in kidney function indicators and oxidative stress levels in the CUO-NPs + SLM group.…”
Section: Discussionmentioning
confidence: 60%
“…The liver of rats treated with CuQ showed histopathological changes, such as dilatation of the sinusoidal spaces, congestion of the centro-lobular vein, infiltration of inflammatory lymphocyte and Kupffer cells, and cell necrosis; previous reports have demonstrated that copper fungicides induced histopathological changes in hepatic tissues (Ghonimi et al, 2022; El-Hak and Mobarak, 2019). In our investigation, the treatment with CuQ induced dose-dependent pathological changes in kidneys as evidenced by tubular and glomerular degeneration and tubular necrosis.…”
Section: Discussionmentioning
confidence: 85%